The effects of bioincising by Physisporinus vitreus on cuo retention and copper element leaching in oriental spruce wood - Davut Bakir; Saip Nami Kartal; Evren Terzi; Ayşe Dilek Dogu (Maderas: Ciencia y Tecnología, 2022)
Since the treatability of Oriental spruce wood (Picea orientalis) with preservative solutions is difficult and considered as a refractory wood species, this study was intended to bring its treatability class by a bioincising process to the level of sapwood of Scots pine (Pinus sylvestris), a desirable wood species for the forest products industry. Bioincising process by Physisporinus vitreus fungus was applied to wood samples from sapwood and heartwood portions of spruce wood. The samples with two different weight loss groups (5–10 % and 10–15 %) in the bioincising process were used to detect changes in treatability with wood preservative solutions caused by the fungus. The bioincised and unincised control samples were treated with either micronized copper quat (MCQ) or alkaline copper quat type D (ACQ-D) wood preservative solutions by either dipping or vacuum methods. Following impregnation with the preservative solutions, the effects of the bioincising process on CuO (copper oxide) retention, and the leaching of Cu (copper) element were determined. The results showed that CuO retention levels increased after the bioincising process. Moreover, there was greater CuO retention in the spruce heartwood samples compared to the spruce and Scots pine sapwood samples. Amount of Cu element released from the Scots pine sapwood samples was found to be lower than that from the spruce sapwood and heartwood samples after the bioincising. process. The results suggest that the bioincising process by P. vitreus in refractory wood species might improve the treatability of wood by Cu-based wood preservatives.